Sport Smart Futsal: Development and Feasibility Evaluation of an Android-Based Educational Game for Basic Futsal Technique Instruction in Junior High School PJOK - Rahma Zaimatul Azhar; Nuur Wachid Abdul Majid; Rhezwan Dhaifullah Romdhoni (FKIP - Universitas Riau, 2026)
Basic futsal technique instruction in Indonesian junior high schools is constrained by limited weekly contact time and the absence of technology-based supplementary media, leaving students with insufficient opportunity to consolidate passing, dribbling, and shooting competencies outside scheduled lessons. This study aimed to develop and evaluate Sport Smart Futsal, an Android-based educational game designed as a supplementary learning medium for Grade VII PJOK students, and to determine student responses to the game. Development followed the four-stage 4D model (Define, Design, Develop, Disseminate), producing a Unity-built game with three technique-specific levels integrating Video, Info, and Quiz functions with embedded gamification elements. Validation was conducted by a content expert and a media expert, followed by small-scale (n = 8) and large-scale (n = 40) student response trials. Content expert validation yielded 90.0% and media expert validation yielded 82.5%, producing an overall average of 86.2% (Very Feasible). Small-scale trial response averaged 91.1% and large-scale trial response averaged 90.1%, with all items rated Very Feasible. Sport Smart Futsal is confirmed as a valid and feasible supplementary learning medium for basic futsal technique instruction, with future research recommended to employ experimental designs measuring direct learning gains.